PARTICIPAÇÃO DOS SUJEITOS PARCIAIS NOS PROCESSOS INDIVIDUAIS MULTIPOLARES - Freire, Deborah Azevedo (2022)
This dissertation aimed to investigate the possibility of renewing the classic participatory model, in the light of the CPC/2015, as a way of adapting it to multipolar processes. This object is closely linked to the research concentration area of the PPGDIR “Process, Techniques and Protenction of Existential and Patrimonial Rights”. The research problem consists in the inadequacy of the model of participation of the civil process in its traditional format to the multipolar processes, marked by the plurality of interests on a certain litigious issue. The work is divided into three chapters. The first chapter aims to demonstrate that the current participatory model is shaped solely to protect bilateral interests. Therefore, an analysis of the current model of participation in the civil process is carried out, presenting its main characteristics. The second chapter aims to identify the research problem, that is, the formation of multipolarity in individual civil proceedings. In the foreground, the phenomenon is conceptualized, separating multipolarity and polycentrism. In the background, is carried out the categorization of multipolarity, according to its origin. In this context is presented examples of different types of multipolar processes. The third chapter focuses on assessing the feasibility of adopting a new participatory model capable of accommodating the multiple interests of the parties in multipolar processes. It analyzes the extent to which procedural flexibility and the free transit of procedural techniques adopted by CPC/2015 can be used as instruments for the renewal of the classic participatory model. The investigation is based on exploratory and bibliographical research, through the analysis of doctrinal material - national and foreign -, jurisprudential and normative, in order to consolidate the theoretical framework sufficient for the conclusion of the proposed research. A deductive syllogistic reasoning is used to, from the examination of the civil procedure system (major premise), extract the conclusion of the possibility of conceiving a new participatory model applicable to multipolar processes (minor premise).